2022
DOI: 10.4081/jbr.2022.10660
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of hydrocarbon-tolerant microalgae in flowback wastewaters produced during hydrofracking of impermeable rocks

Abstract: Huge amounts of Wastewaters (WWs) are produced yearly by the hydrofracking of impermeable rock formations for the extraction of oil or natural gas. Flowback Wastewaters (FWs) are characterized by high contents of inorganic contaminants and hydrocarbons thus representing a relevant threat for the environment. In this work three hydrocarbon-tolerant microalgae have been cultivated in flowback water generated during hydraulic fracturing to investigate their growth kinetics. All three strains could grow in FWs irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In some cases, utilizing a single source of wastewater may not be sufficient for efficient biomass production. For example, it has been shown that, although microalgae can be grown on wastewater generated during hydraulic fracturing of tight petroleum reservoirs, i.e., hydraulic fracturing wastewater (HFWW), biomass yields were quite low due to the extremely poor nutrient content in the growth media [25][26][27][28][29]. The cultivation of the Oklahoma native microalgae strain Picochlorum oklahomensis (PO) in HFWW for 30 days resulted in biomass productivity of only 25 mg. L −1 .…”
Section: Chlorella Vulgarismentioning
confidence: 99%
“…In some cases, utilizing a single source of wastewater may not be sufficient for efficient biomass production. For example, it has been shown that, although microalgae can be grown on wastewater generated during hydraulic fracturing of tight petroleum reservoirs, i.e., hydraulic fracturing wastewater (HFWW), biomass yields were quite low due to the extremely poor nutrient content in the growth media [25][26][27][28][29]. The cultivation of the Oklahoma native microalgae strain Picochlorum oklahomensis (PO) in HFWW for 30 days resulted in biomass productivity of only 25 mg. L −1 .…”
Section: Chlorella Vulgarismentioning
confidence: 99%